Uncovering Genomic Regions Associated with Trypanosoma Infections in Wild Populations of the Tsetse Fly Glossina fuscipes. Issue 3 (1st March 2018) - Gloria-Soria, Andrea; Dunn, W Augustine; Yu, Xiaoqing; Vigneron, Aurélien; Lee, Kuang-Yao; Li, Mo; Weiss, Brian L; Zhao, Hongyu; Aksoy, Serap; Caccone, Adalgisa
Abstract: Vector-borne diseases are responsible for > 1 million deaths every year but genomic resources for most species responsible for their transmission are limited. This is true for neglected diseases such as sleeping sickness (Human African Trypanosomiasis), a disease caused by Trypanosoma parasites vectored by several species of tseste flies within the genus Glossina . We describe an integrative approach that identifies statistical associations between trypanosome infection status of Glossina fuscipes fuscipes ( Gff ) flies from Uganda, for which functional studies are complicated because the species cannot be easily maintained in laboratory colonies, and ∼73, 000 polymorphic sites distributed across the genome. Then, we identify candidate genes involved in Gff trypanosome susceptibility by taking advantage of genomic resources from a closely related species, G. morsitans morsitans ( Gmm ). We compiled a comprehensive transcript library from 72 published and unpublished RNAseq experiments of trypanosome-infected and uninfected Gmm flies, and improved the current Gmm transcriptome assembly. This new assembly was then used to enhance the functional annotations on the Gff genome. As a consequence, we identified 56 candidate genes in the vicinity of the 18 regions associated with Trypanosoma infection status in Gff . Twenty-nine of these genes were differentially expressed (DE) among parasite-infected and uninfected Gmm, suggesting that their orthologs in Gff may correlate with disease transmission. These genes were involved in DNA regulation, neurophysiological functions, and immune responses. We highlight the power of integrating population and functional genomics from related species to enhance our understanding of the genetic basis of physiological traits, particularly in nonmodel organisms.